Bifocal refractive corneal inlay implantation to improve near vision in emmetropic presbyopic patients. Issue 9 (September 2015) - Malandrini, Alex; Martone, Gianluca; Menabuoni, Luca; Catanese, Anna Maria; Tosi, Gian Marco; Balestrazzi, Angelo; Corsani, Chiara; Fantozzi, Marco
Abstract : Purpose : To evaluate the safety and effectiveness of the Flexivue Microlens corneal inlay for the improvement of near vision in emmetropic presbyopic patients. Setting : Ophthalmology Department, Misericordia e Dolce Hospital, Prato, Italy. Design : Prospective interventional case series. Methods : Corneal inlay implantation was performed in nondominant eyes using a 150 kHz femtosecond laser (iFS). Refraction, uncorrected (UNVA) and corrected (CNVA) near visual acuities, uncorrected (UDVA) and corrected (CDVA) distance visual acuities, slitlamp evaluation, wavefront aberrometry, photopic and mesopic contrast sensitivity, anterior segment optical coherence tomography, endothelial cell density, and central corneal thickness measurements were assessed preoperatively and at each postoperative visit. Results : The study evaluated 81 eyes. In 26 eyes, the mean preoperative UNVA and UDVA were 0.76 logMAR and 0.00 logMAR, respectively, compared with 0.10 logMAR and 0.15 logMAR, respectively, 36 months postoperatively. Sixteen (62%) of 26 treated eyes lost more than 1 line of UDVA, and 5 (19%) lost more than 2 lines of UDVA. Two eyes (8%) lost more than 1 line of CDVA at 36 months. The mean binocular UDVA was 0.00 logMAR preoperatively and 0.02 logMAR at 36 months. The mean spherical aberration increased after surgery. Statistically significant differences in the mean mesopic and photopic contrast sensitivities at higher spatial frequencies were found between treated eyes and nontreated eyes. Explantation was performed in 6 treated eyes because of halos, glare, and a reduced UDVA. Conclusion : The corneal inlay might be a safe and effective method of improving UNVA in emmetropic presbyopic patients. Financial Disclosure : Dr. Fantozzi is a member of the Presbia medical advisory board. No other author has a financial or proprietary interest in any material or method mentioned.